The Application of Hypnotherapy on Insomnia Levels in the Elderly at the Panti Sosial Tresna Werdha Budi Luhur Jambi - Rina Oktaria; Suryati Suryati; Ibim Kasmidi; Yeyen Gustina Irawan; Putri Irwanti Sari; Indah Mawarti; Febri Tri Andini; Kintan Resqhita Ekaputri (Jurnal Kesehatan, 2025)
Introduction: Aging is the process of tissue loss or decline in the ability to maintain normal bodily functions. Insomnia is a sleep disorder characterized by difficulty falling asleep, frequent nighttime awakenings and difficulty falling back asleep, waking up too early in the morning, and restless sleep, even with adequate sleep duration. Insomnia can have negative impacts on sufferers, including physical and mental health issues such as heart disease, stroke, diabetes, obesity, depression, and anxiety. Furthermore, insomnia also impacts social and productivity, such as decreased work performance and relationship problems due to emotional instability. Hypnotherapy is a form of healthcare that involves a state of deep relaxation and focus to help patients overcome various problems. In hypnotherapy, the client and hypnotherapist work together to achieve goals. During therapy, the nurse acts as a guide, maintaining full awareness and control over the client. The client will remain conscious during the session, be able to hear the therapist's voice, remember what happened, and even reject suggestions if they don't align with their values. Method: This research is a descriptive case study design. The subjects were two elderly individuals who served as respondents. The study was conducted in the working area of the Panti Sosial Tresna Werdha Budi Luhur Jambi on May 27-29, 2025. Results: Based on the results of the study that has been conducted for 3 days in 1 week for 45 minutes, it was concluded that before the application of hypnotherapy, the results obtained from the two respondents were Mr. S score of 33 and Mr. N score of 35, indicating that both were categorized as severe insomnia. After the application of hypnotherapy, the results obtained from the two respondents were Mr. S score of 22 and Mr. N score of 24, indicating a change that was categorized as mild insomnia. Conclusion: Hypnotherapy significantly impacted the change in insomnia scores, as evidenced by the difference in insomnia scores before and after the intervention. This recommendation is for nurses to implement independent nursing interventions through complementary hypnotherapy.